Reshaping the agenda of the European Commission for the health systems and policy research in Europe within Horizon 2020 (Epidemiology, Biostatistics, and Public Health, 2022)
In 2012 the European Regional Office of WHO published a new health policy strategy, Health 2020, and an accompanying European Action Plan [1, 2], with both documents since being endorsed by the 53 member states. Following consultation with member states, a series of overarching targets have been established in the three areas of Health 2020: i) reducing the burden of disease and risk factors;  ii) enhancing health and well- being; and iii) improving governance and systems for health. The WHO is now working with member state governments to develop ‘Regional’ Health 2020 targets [3, 4].If Health 2020 is to achieve these goals, the actions that flow from it must be based on the best...